Penghormatan Hak-Hak Penyandang Disabilitas Melalui Kebijakan Kuota Kerja di Indonesia - Annur, Farashaty; Sjafari , Agus; Riswanda, Riswanda (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
This article discusses the issue of people with disabilities related to the quota system policy for hiring people with disabilities in Indonesia by referring to Law No. 8/2016 Article 53 stipulates the responsibility of the quota policy for hiring workers with disabilities, which is 1% for private companies and 2% for the government and state-owned enterprises. However, many current programs and services have not achieved their goal of assisting all persons with disabilities. Policies, programs, and services for persons with disabilities are not yet fully inclusive, integrated (across sectors), and adequate due to the many data issues and characteristics of persons with disabilities. Increasing the involvement of people with disabilities in development is therefore a challenge.